A constituição do sujeito biólogo e as formas de poder-controle organizacional em universidades públicas no Estado do Paraná - Gois, Pedro Henrique de (2012)
From a theoretical base grounded in the philosophy of Michel Foucault, we present an overview of the constitution of subject biologist at two universities in Parana. To develop this propose, the power relations experienced by the subjects were analyzed, in order to demonstrate how these relationships, working through the design of control devices, become more sophisticated and pervasive in the social space. We sought to characterize the constitution of the subject-biologist through the crossings that the individual experiences in contact with these devices in the organizational space. For Foucault (2009), the operation of power assumes that individuals are free, working in a space of possibilities in which to seek subjectively, being crossed by mechanisms that enable and restrict freedom. Fundamentally, the relation power constitutes itself as strategic relations of imposition and resistance, either reinforced or opposed by the subject in a shift of forces seeking to maintain or create mechanisms to ensure the continuity of the exercise of power. From this perspective, we understand it as organizational power-control mechanisms set out by Foucault as experienced by the subjects in their professional practice, drawing on elements of institutions such as suitability of the subject to the institutional structure. The resistance movements and reinforcement of such devices are shown to be involved in the practical constitution of the subject, which is in higher education institutions an important area of professional actions, because experience and is actively influenced by mechanisms of power-control organization. The analytical perspective adopted in this dissertation sought to focus on the discursive formations as Foucault states seeking to highlight the peculiarity of space and time they are constructed and arranged speeches by the subjects. Research data included documents and legislation relevant to the biology scientific field, as well as forty-two interviews with professional's biologists at the University of Maringá State and Federal University of Parana, equally sampled in both institutions. The analysis sought to demonstrate the operation of power relations among individuals and institutions in which biologists operate, highlighting how this experience influences the constitution of subjects. In conclusion, critically analyzing the speeches, it was noted that biologists interviewed request nowadays a better recognition and professional differentiation, through the constraints and challenges they face on the bureaucratic structure of the universities in which they operate. Another dimension is the identification of prominent professionals in the biological area, especially highlighting many opportunities for personal and professional development in this field of knowledge. Thus, despite the restrictions inherent to public universities, they shape strategies to solve such identified problems, at the same time seeking to establish themselves professionally, developing mechanisms of confrontation and opposition to the limitations they experience.